A meta-analysis of self-assessment and language performance in language testing and assessment. (April 2021) - Li, Minzi; Zhang, Xian
This meta-analysis explores the correlation between self-assessment (SA) and language performance. Sixty-seven studies with 97 independent samples involving more than 68, 500 participants were included in our analysis. It was found that the overall correlation between SA and language performance was .466 ( p  < .01). Moderator analysis was performed to evaluate the moderating effects of a number of variables that are believed to play important roles in SA. Six moderators were found to have significant moderating effects, including SA criteria type, presence and form of SA criteria, SA instruments, training, total number of items in the SA instrument, and reliability of SA instruments . However, no significant moderating effect was identified for external measures, language skills, order of assessment, reliability of external measures, and number of Likert-scale levels . These findings offer a number of implications for improving the SA–performance correlation.